SHOT DESKRIPTIF SEBAGAI ELEMENVISUAL PROGRAM DOKUMENTER KERIS : REFLEKSI BUDAYA J AWA - Sugito, S; Prasetyo, Andry (Capture : Jurnal Seni Media Rekam, 2012)
One of the works of art and cultural traditions of Indonesia that have a high value isKris.Kris is a product of original culture created by the ancestors of Indonesia.Apart from beinga piece of art that has a high value and full of symbolic meanings,the Javanese community is stillwith confidence Kejawen believe Kris has a strength,magical power that has an influence on thelife of its owner.The documentary program is the theme of the existence of art and culturaltraditions in the midst of modern society life activities. This work has the characteristicsedutainment,meaning that in addition to providing entertainment also have purpose to provideeducation or knowledge to the audiences.The idea of this documentary is the story of theJavanese community relations with Kris, in any ceremonial activities and rituals performed bythe Javanese community,Kris never comes off as the completeness of culture that should not beabandoned.The use of shot-shot descriptive meaning the use shot more varied such as, panshots, follow shots, tracking shots, low shots, high shots, over-shoulder shot, is needed in themaking of this documentary,because shooting is mostly done on an event without scenario ordirect camera. Type of shot that is widely used among others: Long shot with reason andpurpose to be flexible to follow the area or wide when the scene moving fast, to show wherethe scene is located (showed a), to indicate progress, as well as to show how to position thesubject has a relationship with others.Type medium shot, shot like this type most commonlyencountered in film and television.This type of shot is the most save,because there is no specialemphasis to the object.Type close shot or close-up function to create a suppressive effect,withsolid images.Keywords :Documentary film,Kris,and Java culture